2005
DOI: 10.1177/0022022105275962
|View full text |Cite
|
Sign up to set email alerts
|

Values and their Relationship to Environmental Concern and Conservation Behavior

Abstract: Recent research has examined the relationship between values and attitudes about environmental issues. Findings from these studies have found values of self-transcendence (positively) and self-enhancement (negatively) to predict general concern for environmental problems. Other recent findings have differentiated between environmental attitudes based on concern for self (egoistic), concern for other people (social-altruistic), and concern for plants and animals (biospheric).This article reports the results fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
693
6
34

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 884 publications
(775 citation statements)
references
References 39 publications
42
693
6
34
Order By: Relevance
“…This preference applied the stronger the more ecofriendly the consumer. This result is in line with previous research showing that ecologically aware consumers tend to behave eco-friendly (e.g., Bang et al, 2000;Schultz et al, 2005). The innovative part lies in the positioning of WPC in the continuum between solid wood and full plastics.…”
Section: Discussionsupporting
confidence: 91%
“…This preference applied the stronger the more ecofriendly the consumer. This result is in line with previous research showing that ecologically aware consumers tend to behave eco-friendly (e.g., Bang et al, 2000;Schultz et al, 2005). The innovative part lies in the positioning of WPC in the continuum between solid wood and full plastics.…”
Section: Discussionsupporting
confidence: 91%
“…Cultures and individuals differ in the weight they give to each of these. However, both of these dimensions are strong predictors of risk perceptions and concern with environmental issues (90)(91)(92)(93)(94). Early theoretical expectations have suggested that deliberative processes might make people more altruistic by encouraging them to see the point of view of others, and there is some evidence in support of the argument (95)(96)(97).…”
Section: Why Scientifically Informed Deliberation Is Difficultmentioning
confidence: 99%
“…Prior research indicates that individuals who value the well-being of larger communities-i.e., those high in self-transcendence-are more likely to harbor pro-environmental attitudes and take pro-environmental action than individuals who value personal gain and status-i.e., self-enhancement (e.g., Gagnon Thompson and Barton 1994;Karp 1996). Thus, people with strong selftranscendent value orientations tend to be more concerned about the environment and more likely to act compared to those who prize self enhancement (e.g., Garvill 2002, 2003;Schultz et al 2005;Schultz and Zelezny 1999;Slimak and Dietz 2006;Steg and de Groot 2012;Stern et al 1995;see de Groot and Steg 2008 for a review).…”
Section: Valuesmentioning
confidence: 99%